Combined osimertinib, dabrafenib and trametinib treatment for advanced non-small-cell lung cancer patients with an osimertinib-induced BRAF V600E mutation. (August 2020) - Meng, Pei; Koopman, Bart; Kok, Klaas; ter Elst, Arja; Schuuring, Ed; van Kempen, Léon C.; Timens, Wim; Hiltermann, T. Jeroen N.; Groen, Harry J.M.; van den Berg, Anke; van der Wekken, Anthonie J.
Highlights: BRAF V600E causes osimertinib resistance in EGFR-mutant NSCLC patients. Concurrent treatment with osimertinib and dabrafenib/trametinib was effective. A reduced dose of dabrafenib/trametinib is recommended due to multi-drug toxicity. Brain metastasis might influence PFS/OS time of the combined treatment. Abstract: Introduction: Previous studies have reported an acquired BRAF V600E mutation as a potential resistance mechanism to osimertinib treatment in advanced NSCLC patients with an activating mutation in EGFR . However, the therapeutic effect of combining dabrafenib and trametinib with osimertinib remains unclear. Here we report treatment efficacy in two cases with acquired BRAF V600E mutations. Methods: Two patients with an EGFR exon 19 deletion and a T790 M mutation, both treated with osimertinib, acquired a BRAF V600E mutation at disease progression. Following the recommendation of the molecular tumor board, a concurrent combination of dabrafenib and trametinib plus osimertinib was administered. Results: Because of toxicity, one patient ultimately received a reduced dose of dabrafenib and trametinib combined with a normal dose of osimertinib. Clinical response in this patient lasted for 13.4 months. Re-biopsy upon tumor progression revealed loss of BRAF V600E and emergence of EGFR C797S. The other patient, treated with full doses of the combined therapy, had progression with metastases in lung and brain one month after starting therapy. Conclusion: BRAF V600E may be a resistance mechanism induced by osimertinib in EGFR- mutated advanced NSCLC. Combined treatment using dabrafenib/trametinib concurrently with osimertinib needs to be explored for osimertinib-induced BRAF V600E mutation.